Using Astragalus membranaceus (Fisch.) Bge. To Treat Skin Diseases: Comparison of Traditional Uses and Research Results - Yun, Chanyong; Kim, Hyungwoo (Pharmacognosy Reviews)
Background: Astragalus membranaceus (Fisch.) Bge. (AM), a member of restoratives for invigoration qi (補氣藥), has been used to treat patients with skin diseases in the framework of traditional medicine. The major efficacies of AM related to skin diseases are tonifying defensive qi and securing the exterior (益衛固表), expelling toxins and pus (托毒排膿), and promoting tissue regeneration and wound healing (生肌斂瘡). Materials and Methods: We investigated the traditional usages of AM described in the textbook and encyclopedia, and we also investigated scientific research using PubMed and the National Digital Library of Korea. Results: In our opinion, tonifying defensive qi and securing the exterior effect of AM is related to the photoprotective, antiaging, and protecting effects on normal skin tissue. Expelling toxins and pus and promoting tissue regeneration and wound healing effects are closely related to the anti‑inflammatory effects and promoting healing of wounds or ulcers on the body surface, respectively. In addition, astragaloside IV, formononetin, calycosin, cycloastragenol (TA‑65), and gamma‑aminobutyric acid were the major components related to therapeutic effects of AM on skin diseases. Conclusion: The therapeutic effects of AM on skin diseases were divided into three categories according to the theory of traditional medicine, and its effects in each category can be explained by scientific experiments.
Keywords: Astragalus membranaceus; dermatology; herbal medicine; skin disease; traditional Chinese medicine